Storytelling Method Influence on the Understanding of Flood Mitigation in Children Aged 5-6 Years in Wanasalam Sub-district - Haryani, Arni; Fadlullah, Fadlullah; Rosidah, Laily (Universitas Pendidikan Indonesia Kampus Serang, 2023)
Flood mitigation is crucial to be introduced in early childhood learning, considering that early childhood victims are vulnerable to disasters. Flood mitigation is vital since the disaster will impact health, physical condition, and continuity of education. This research aims to find out to what extent the effect of the storytelling method on the understanding of flood management in early childhood. This study used a quantitative approach with the experimental method by two samples, namely the experimental and the control groups. Each group consisted of 20 children who were given different treatments and then provided a questionnaire to measure the child's ability to understand disaster mitigation. Based on the calculation results of the paired sample t-test in the experimental group, the Sig (2-Tailed) had a value of 0.000 0.05, so there was a significant effect; thus, H0 was rejected, and H1 was accepted. Furthermore, after being given treatment in the experimental group from pre-test to post-test, the change from pre-test to post-test increased by 31.45. Meanwhile, the control group's change from pre-test to post-test rose by 12.30. It is also known that the most significant change occurred in the experimental group with the treatment method of telling stories about understanding flood mitigation. For this reason, it can be concluded that there is an effect of the storytelling method on flood mitigation in early childhood. Storytelling could be an appropriate alternative to introduce awareness in another disaster mitigation.